PENGARUH MANAJEMEN WAKTU TERHADAP KEDISIPLINAN MAHASISWA DALAM MENYELESAIKAN TUGAS PERKULIAHAN PADA PROGRAM STUDI PGSD DI ERA DIGITAL - Andini, Ayu; Miftahurrahma; Ainun Sari, Indira; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between time management and student discipline in completing academic assignments among students of the Elementary School Teacher Education Program (PGSD) in the digital era. The development of digital technology has provided convenience in the learning process, but it has also created distractions that may affect students’ academic discipline. This research employed a quantitative approach using descriptive and associative methods. The sample consisted of 39 PGSD students. Data were collected through questionnaires using a Likert scale, observation, and documentation. Data analysis was conducted using validity, reliability, normality, and Spearman Rank correlation tests. The results showed that all research instruments were valid, with r-count values higher than the r-table value of 0.316, and reliable, with a Cronbach’s Alpha value of 0.856. The descriptive analysis indicated that students’ time management was in the moderate category with a mean score of 23.77, while student discipline was in the fairly high category with a mean score of 29.26. The normality test showed that the data were normally distributed with a significance value of 0.913 > 0.05. The Spearman Rank correlation test produced a correlation coefficient value of 0.764 with a significance value of < 0.001, indicating a positive and significant relationship between time management and student discipline. The better the students’ ability to manage their time, the higher their level of discipline in completing academic assignments in the digital era.